Catalogue of the Syrphidae of Egypt (Diptera) - El-Hawagry, Magdi S.; Gilbert, Francis (Zootaxa, 2019)
All known Egyptian taxa of the family Syrphidae (flower flies or hover flies) are systematically catalogued. A total number of 51 species belonging to 22 genera, 7 tribes and 2 subfamilies has been treated, including eight species that are listed as unconfirmed records from Egypt. Data for this study have been compiled from both available literature and specimens collected from different Egyptian localities by the authors or preserved in the main Egyptian insect collections. Old World synonymies, type localities, world distributions by biogeographic realm(s) and country, Egyptian localities and activity periods are provided. Remarks on habitat, habits and biology of particular species are provided as well. Two species, Melanostoma scalare (Fabricius) and Eristalis arbustorum (Linnaeus) are recorded for the first time from Egypt.